Isolation and identification of Bacillus species from soil and assessment of antimicrobial properties - Basi-Chipalu, Shradha; Sthapit, Pallavi; Maharjan, Aastha (Scientific World, 2023)
The emergence of multi drug resistant pathogens such as Methicillin resistant Staphylococcus aureus (MRSA) has become a threat to public health. Thus, the development of new antibiotics has become a global concern. Many scientists are attracted towards discovery of new antimicrobial agents from microbial sources. The aim of this study is to isolate potential Bacillus species from soil for the production of antimicrobial substance. During the study, 20 soil samples were collected from various areas of Kathmandu valley. A total of 70 Bacillus isolates were identified by morphological and biochemical characteristics. Altogether 39 isolates were able to produce antibacterial extract when it was grown in Trypticase soya broth (TSB) at 37°C for 48 h. The antimicrobial activity was tested against test organisms like Escherichia coli, Klebsiella pneumoniae, Salmonella, Pseudomonas, Staphylococcus aureus and Candida by Agar well diffusion method. All of the extracts showed zone of inhibition against E. coli except 6 extracts (E39, E43, E36, E25, E45 and E46). The highest zone of inhibition was shown by extract B68 with 11 mm. Only one extract (E62) was able to inhibit the growth of Pseudomonas. The extract from Bacillus isolate (E35) showed highest zone of inhibition against S. aureus (6mm). The protein nature of the extracts was determined by Biuret and Ninhydrin tests. The extracts were relatively stable to heat treatment and unstable to surfactants like 70% methanol, 2-propanol and ethylacetate. The study revealed that soil is a good source for the potential antimicrobial producer bacteria.